THE ANALYSIS STUDY OF ASSOCIATION OF TYPE 2 DIABETES MELLITUS AND SKIN CANCER : A COMPREHENSIVE SYSTEMATIC REVIEW - Juwita, Tia Alviani; Siregar, Indah Sari (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The correlation between type 2 diabetes and skin cancer has been established, with elevated blood glucose levels and increased insulin levels associated with a higher risk of certain malignancies, such as nonmelanoma skin cancer. However, the impact of insulin therapy on cancer risk in individuals with type 2 diabetes is generally not significant. Understanding this correlation can help develop effective strategies for managing both conditions. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. A number of websites, including ScienceDirect, PubMed, and SagePub, were utilized to gather the literature. Result: The study looked at more than 100 publications using reputable sources including Science Direct, SagePub, and PubMed. After it was decided that eight publications needed greater investigation, a more extensive review of the entire literature was carried out. Conclusion: The incidence of skin cancer in diabetic individuals is higher in those aged 60 and older, with males more likely to develop non-melanoma skin cancer (NMSC) and melanoma. Risk factors include sex, comorbidities, immunosuppression status, and socioeconomic status. Insulin therapy can lower the risk of NMSC, but further studies are needed to understand differences in incidence.